Seeing is Believing: Do Analysts Benefit from Site Visits - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2014)
Using the unique data of analysts’ site visits to Chinese listed companies, we examine whether and how analysts’ site visits help improve their forecast performance. We find that the forecast accuracy of analysts improves after they visit the target firms and this improvement still holds after controlling for the concurrent change in the forecast accuracy of analysts who do not conduct site visits. Such an improvement is more pronounced for firms with better corporate governance; for more experienced analysts; and for firms with higher earnings volatility. Moreover, the improvement of forecast accuracy is less pronounced when current site visits are preempted by preceding site visits, and when there are other non-analyst visitors. Furthermore, we find that local analysts benefit more from corporate site visits than non-local analysts. Lastly, we document a larger market reaction to earnings forecasts issued by visiting analysts than those issued by non-visiting analysts.